The role of law in the governance of the internet - Christoph Engel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
The Internet epitomizes globalisation. There are not many international treaties on Internet issues so far. For the time being, governance of the Internet by law will thus basically have to be governance by national law. Most cyber scholars are therefore in the business of exploring alternative governance tools. The typical approach is hybrid, combining state with non-state inputs, and using soft forms of governance, not command and control regulation. Against this background, this papers makes two related points. The preoccupation of the legal discourse with globalisation is partly misleading. The Internet has more and even more profound challenges to governance by law: the libertarian beliefs of many Internet activists; the egalitarian culture of Netizens; the ultra high speed of evolution; and the almost complete decontextualisation of Internet communication. Despite these many and profound challenges, Internet governance by law is not pointless. Separately, the law is able to parry each of these challenges, albeit to a varying degree. The law comes in more troubled waters, if these challenges compound. But even then, there is room left for the law. Policy makers should thus not rule the law out a limine. They should properly weigh the many advantages governance by law has over alternative institutions.
Keywords: K33; K20; H73; 330; governance by law; command and control regulation; cyberlaw; globalization; governing the egalitarians; governing decontextualized behaviour; internet regulation